Letter from Stephen Reinhardt - Stephen Reinhardt:::::: (1969)
In this February 10, 1969 letter, Stephen Reinhardt reports on the Democratic National Committee meeting in Washington, D.C., highlighting the election of Senator Fred Harris as National Chairman and efforts to modernize and reform the party. He describes new resolutions and committees, including support for abolishing the Electoral College, reforms to delegate selection, and the creation of policy, rules, and equal rights bodies. Reinhardt also discusses controversy over seating Georgia members, notes California's involvement in national leadership, and invites suggestions to support California Democrats.